Study on south-west monsoon rainfall characteristics in arid zone of Haryana - SINGH, MAHENDER; SINGH, RAM; NIWAS, RAM; SAHRAWAT, K. D. (MAUSAM, 2003)
The daily rainfall data of arid zone for a period of 50 years (1946-95) at three locations. Hisar, Bhiwani and Sirsa were analyzed to find out characteristics of south-west monsoon. Mean onset date was observed 4 July at Hisar and Bhiwani with standard deviation of 7 to 9 days respectively, whereas 7 July at Sirsa with standard deviation of 9 days. The onset date of monsoon was inversely related to amount of rainfall at all stations under study. The mean withdrawal dates of south-west monsoon were 15 September at Hisar and Bhiwani and 11 September for Sirsa with standard deviation of 9 days at all three locations. The withdrawal dates also showed inverse and significant correlation with rainfall amount. The mean number of rainy days at Hisar, Bhiwani and Sirsa were 18, 17 and 13 with standard deviation of 5, 6 and 6 days, respectively.